Manufacturing T cells in hollow fiber membrane bioreactors changes their programming and enhances their potency. (1st January 2021) - Yoo, Seung Mi; Lau, Vivan W.C.; Aarts, Craig; Bojovic, Bojana; Steinberg, Gregory; Hammill, Joanne A.; Dvorkin-Gheva, Anna; Ghosh, Raja; Bramson, Jonathan L.
ABSTRACT: Engineered T cell therapies have revolutionized modern oncology, however processes for manufacturing T cell therapies vary and the impact of manufacturing processes On the cell product is poorly understood. Herein, we have used a commercially available hollow fiber membrane bioreactor (HFMBR) operated in a novel mode to demonstrate that T cells can be engineered with lentiviruses, grown to very high densities, and washed and harvested in a single, small volume bioreactor that is readily amenable to automation. Manufacturing within the HFMBR dramatically changed the programming of the T cells and yielded a product with greater therapeutic potency than T cells produced using the standard manual method. This change in programming was associated with increased resistance to cryopreservation, which is beneficial as T cell products are typically cryopreserved prior to administration to the patient. Transcriptional profiling of the T cells revealed a shift toward a glycolytic metabolism, which may protect cells from oxidative stress offering an explanation for the improved resistance to cryopreservation. This study reveals that the choice of bioreactor fundamentally impacts the engineered T cell product and must be carefully considered. Furthermore, these data challenge the premise that glycolytic metabolism is detrimental to T cell therapies.